(untitled) (Journal of Information Technologies in Education (ITE), 2011)
Diagnostic testing is considered as a means of a detailed study of educational achievement of students with a purpose of individual choice of methods and forms of learning. The demands to subsystem testing educational achievements in the computer-oriented system of pedagogical diagnostics are substantiated on the base of the system of the methodological, procedural-organizational, psychological-pedagogical requirements to pedagogical diagnosis. According to this demands, the structure of test database is designed so as to provide variability of the test items with preserving its representation regarding the content of educational material. Adaptive algorithm of testing and algorithm of test results interpretation with vector processing of the data elements by the educational levels and educational achievements are also designed.